2010
DOI: 10.1128/iai.01021-09
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Duration of Protection in Campylobacter jejuni Experimental Infection in Humans

Abstract: A human Campylobacter jejuni infection model provided controlled exposure to assess vaccine efficacy and investigate protective immunity for this important diarrheal pathogen. A well-characterized outbreak strain, C. jejuni 81-176, was investigated using a volunteer experimental infection model to evaluate the dose range and duration of protection. Healthy Campylobacter-seronegative adults received C. jejuni strain 81-176 via oral inoculation of 10 5 , 10 7 , or 10 9 CFU (5 adults/dose), which was followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 53 publications
5
75
1
Order By: Relevance
“…Our findings are similar to those of previously published studies showing that an oral booster dose given at a time of active mucosal immunity results in lower or similar levels of antibody-secreting cells (ASC) and serum IgA responses to CTB (cholera toxin B) (15,(24)(25)(26). Similar blunting of responses has also been seen with Campylobacter (27) and Shigella (28) volunteer challenge models.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings are similar to those of previously published studies showing that an oral booster dose given at a time of active mucosal immunity results in lower or similar levels of antibody-secreting cells (ASC) and serum IgA responses to CTB (cholera toxin B) (15,(24)(25)(26). Similar blunting of responses has also been seen with Campylobacter (27) and Shigella (28) volunteer challenge models.…”
Section: Discussionsupporting
confidence: 81%
“…Since there was only one subject who was not protected from diarrhea when rechallenged, our data were not able to identify such a marker for protection in the present study. Given the high level of interest in ETEC vaccine development, the field could benefit from a longer follow-up after initial infection similar to the challenge-rechallenge studies performed with Campylobacter (27) which may give more insights into correlates of long-term immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an association between dose and occurrence of disease was observed in humans experimentally infected with C. jejuni strain 81-176. In addition, exposure to C. jejuni strain 81-176 offered only short-term protection (7). This can be reconciled by the fact that the severity of disease, dose-response relationship, and illness/infection ratio are dependent, at least in part, on the strain used.…”
Section: Jejuni and C Coli Are Established Causes Of Diarrhea Inmentioning
confidence: 92%
“…Based on the relatively high inoculum required to elicit diarrhea in a sufficient number of subjects and the inverse association between diarrhea risk and baseline LT IgG titers, one may hypothesize that inclusion of serologic screening, as has been utilized for Campylobacter jejuni challenge model development [59,60], may decrease the required inoculum. None of the studies reviewed here reported serologic screening of potential study participants.…”
Section: Ethicsmentioning
confidence: 99%